THE RELATIONSHIP BETWEEN DIET AND THE HEALING PROCESS OF SURGICAL WOUNDS IN POST SECTIO CAESAREA PATIENTS AT KARUNIA KASIH HOSPITAL IN 2023 - Marsinta, Nur Aulia; Rahmadhena, Melisa Putri (HEARTY, 2025)
Background: Diet greatly influences a person's nutritional status, a good diet can improve nutritional status. A state of deficient nutritional status occurs because the body lacks one or several types of nutrients needed, such as the amount of nutrients consumed is insufficient and the frequency and quality are lacking. The trend for caesarean sections is increasing every year. One of the obstacles that often occurs in mothers after caesarean section is abstinence from food after giving birth. If the mother does not consume enough nutrition, it will result in the wound not drying quickly so that wound healing takes a long time. How to recover after a cesarean section is related to mobilization, nutrition, activity stress and personal hygiene. Research Objective: To determine the relationship between eating patterns and the healing process of surgical wounds in post caesarean section patients at Karunia Kasih Hospital. Research Method: This research used a cross sectional approach design with a sample of 98 people. Data techniques include univariate analysis using frequency distribution and bivariate analysis using statistical calculations from the SPSS program. Research Results: The results of this study show that there is a relationship between diet and the surgical wound healing process in post-sectio caesarea patients at Karunia Kasih Hospital, with the chi square test being (0.009) < α (0.050) indicating that diet influences the surgical wound healing process. Conclusion and Suggestions: there is a relationship between diet and the healing process of surgical wounds in post-cesarean section patients at Karunia Kasih Hospital in 2024. Suggestions. It is hoped that the hospital can become a reference for providing coaching and training to health workers to provide more active education to post-section patients so that they are able to maximum in the healing process.